Advances and Applications of Clostridium Co-culture Systems in Biotechnology - Du, Yuanfen; Zou, Wei; Zhang, Kaizheng; Ye, Guangbin; Yang, Jiangang (Frontiers in Microbiology, 2020)
Clostridium spp. are important microorganisms that can degrade complex biomasses such as cellulose, which is a widespread and renewable natural resource. Co-culturing Clostridium spp. and other microorganisms is considered to be a promising strategy for utilizing renewable feedstocks and has been widely used in biotechnology to produce bio-fuels and bio-solvents. In this review, we summarize recent progress on the Clostridium co-culture system, including system unique advantages, composition, products, and interaction mechanisms. In addition, biochemical regulation and genetic modifications used to improve the Clostridium co-culture system are also summarized. Finally, future prospects for Clostridium co-culture systems are discussed in light of recent progress, challenges, and trends.